Helping Others as a Response to Reconcile a Criminal Past: The Role of the Wounded Healer in Prisoner Reentry Programs. (January 2015) - LeBel, Thomas P.; Richie, Matt; Maruna, Shadd
Anecdotal evidence suggests that many of the staff members working for prisoner reentry programs are formerly incarcerated persons. Moreover, criminologists have written that the strengths-based role of the "wounded healer" or "professional ex-" is exemplified by released prisoners who desist from a deviant career by replacing it with an occupation as a paraprofessional, lay therapist, or counselor. Despite these observations, there is a paucity of research about formerly incarcerated persons employed by agencies that provide reentry-related programming. This study begins to fill this gap by examining whether, how, and why the staff members of prisoner reentry programs differ from the clients. Characteristics of formerly incarcerated persons thought to be related to desistance and reconciling a criminal past such as overcoming stigma, prosocial attitudes and beliefs, active coping strategies, psychological well-being, and satisfaction with life are examined. Findings support the notion that the wounded healer or professional ex- role is related to desistance and can potentially transform formerly incarcerated persons from being part of "the problem" into part of "the solution" to reduce crime and recidivism.